Simultaneous quantification of six flavonoids in four Scutellaria taxa by HPLC-DAD method - Bardakci, Hilal; Acar, Ebru Turkoz; Kirmizibekmez, Hasan (SOC BRASILEIRA FARMACOGNOSIA, 2019)
The objective of this study was to develop and validate a new HPLC method to quantify several flavonoids in the methanol extract prepared from the aerial parts of four Scutellaria L. taxa from flora of Turkey. A simple, sensitive and precise reversed phase HPLC-DAD method was developed and validated for simultaneous determination of six main flavonoids

scutellarein 7-O-beta-d-glucopyranoside, hispidulin 7-O-beta-d-glucuronopyranoside, apigenin 7-O-beta-d-glucopyranoside, hispidulin 7-O-beta-d-glucopyranoside, luteolin and apigenin. All standard compounds showed a good linearity (R-2>0.999) in a relatively wide concentration range (1-120 mu g/ml). The limit of detection of the compounds was in the range of 0.016-1.883 mu g/ml and the limit of quantification was in the range of 0.232-3.368 mu g/ml. The recoveries of the selected compounds were calculated in the range of 92.20-107.93\%. The amounts of flavonoids showed variation in the extracts. The developed method was found to be accurate, precise, reproducible, and can be successfully applied to identify and quantify the flavonoid composition of Scutellaria species. (C) 2019 Sociedade Brasileira de Farmacognosia. Published by Elsevier Editora Ltda.
Keywords: Flavonoids; HPLC-DAD; Scutellaria albida ssp. albida; Scutellaria hastifolia; Scutellaria orientalis ssp. pinnatifida; Scutellaria velenovskyi